Lessons from the Mass Production of Wolbachia-infected Aedes aegypti for Egg Release in the Sleman and Bantul Districts of Yogyakarta - Fitriana, Iva; Nurhayati, Indah; Arianto, Budi; Chusnaifah, Defriana Lutfi; Utami, Indira Diah; Purwaningrum, Nabhela Ayu; Saraswati, Utari; Supriyati, Endah; Utarini, Adi; Ahmad, Riris Andono; Indriani, Citra; Arguni, Eggi; Tantowijoyo, Warsito (Universitas Gadjah Mada, 2024)
An efficacy study on wMel Wolbachia-infected Aedes aegypti technology conducted by the World Mosquito Program (WMP) Yogyakarta showed the reducing of dengue incidence in Yogyakarta City. Following this successful result, the intervention was scaled up into two neighbouring districts: Sleman and Bantul. This paper describes our experience in mass production for providing release material for a larger area to reach the deployment target, which includes insectary requirements, mass production protocols, and diagnostic screening. This review may serve as a reference guidance for national mass production for wMel Wolbachia-infected Ae. aegypti.